Odpowiedzi

2009-11-20T15:23:16+01:00
X³ - 2x² - x + 2 = 0
x²(x - 2) - (x - 2) = 0
(x² - 1)(x - 2) = 0
(x - 1)(x + 1)(x - 2) = 0
x₁ = 1
x₂ = 2
x₃ = -1

x⁴ - 5x³ + x² + 11x + 4 = 0
(x³ - 6x² + 7x + 4)(x + 1) = 0
(x² - 2x - 1)(x - 4)(x + 1) = 0
x₁ = 1 - √2
x₂ = 1 + √2
x₃ = -1
x₄ = 4

(x-2)(-x²-x-2)<0
x₁ = 2
x ∈ (2; ∞)
1 5 1
2009-11-20T15:35:38+01:00
X³ -2x² - x +2 = 0
x(x² -1) -2(x² -1) = 0
(x - 2)(x² -1) = 0
(x -2 )(x -1)(x +1) = 0
x =2 lub x =1 lub x = -1
---------------------------
1 3 1
2009-11-20T17:17:41+01:00
X3-2x2-x+2=0
x(x2-1)-2(x2-1)=0
(x-2)(x2-1)=0
(x-2)(x-1)(x+1)=0
x=2 lub x=1 lub x=-1
nie wiem czy dobrze